(untitled) (Sport Science Research, 2025)
The article discusses the improvement of the methodology for bringing Wushu athletes to a state of the highest readiness. The purpose of the research is to scientifically substantiate and develop an effective methodology for ensuring the highest readiness of martial artists for competitions. As a result of a retrospective analysis of scientific and methodological literature and training programs of Wushu athletes, pedagogical observation of the results of the questionnaire and focus group, it was determined that planning the preparatory period for the main competitions should take into account the relationship between the education of physical qualities and the development of self-confidence, as well as their complex impact on pre-competitive training. The factors determining the high level of anxiety among martial artists in preparation for competitions are revealed: low level of physical and psychological readiness of martial artists for competitions; insufficient confidence of martial artists in their abilities and lack of self-regulation skills to relieve excessive anxiety in the preparatory period. The effectiveness of the developed methodology of using special physical training tools to reduce the level of anxiety among athletes and bring them to combat readiness has been proven. The results of the study have practical implications for the work of the coaching and teaching staff of children’s and youth schools and sports clubs.